PENGARUH E-RESOURCES TERHADAP PRESTASI AKADEMIK YANG DIMEDIASI OLEH PERCEIVED USEFULNESS - Anton Risparyanto; R. Edi Fitriyanto (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
Academic achievement directly or indirectly (through perceived usefulness mediation). influenced by the availability of electronic information sources (e-resources). This study aims to determine the significant value of probability: (1) The effect of electronic information sources (e-resources) on perceived usefulness: (2) The effect of perceived usefulness on academic achievement and (3) The direct or indirect influence of electronic information sources (e-resources) ) library on academic achievement. Furthermore, the results of this study are expected to be used as a recommendation material for conceptual formulation in improving student academic achievement through electronic information sources (e-resources) and perceived usefulness. This quantitative research consists of three variables including: electronic information sources (e-resources) as the independent variable, academic achievement as the dependent variable and functioning as an intervening variable, namely perceived usefulness. 100 samples of data were taken by probability from a population of 134. The data analysis used included the classic assumption test, the t hypothesis test and the Determinant (R2) test through path analysis. The results of the study show that: (1) Electronic information sources (e-resources) have a significant effect on perceived usefulness) as indicated by the probability p-value of 0.000 with a t-value of 6,757 which is less than 0.05 (p-value = 0.000 < 0.05); (2) Perceived usefulness has a significant effect on academic achievement with a t-value of 4,579 and a probability of less than 0.05 (p-value = 0.000 <0.05); (3) So directly electronic information sources (e-resources) have a significant effect on academic achievement by 24.2%. with a p-value probability of 0.000 with a t-count value of 6,757 less than 0.05 (p-value = 0.000 <0.05) Likewise, indirectly (through perceived usefulness mediation) a significant effect on academic achievement is shown with a t value of 3.78294426 with a std error of 0.0812436 and a significant probability value of 0.00015498 p-value of 30.734%.